From atherosclerosis to cardiovascular incidents – intervention at children and youth with hypertension - Bryl, Wiesław; Hoffmann, Karolina (Przewodnik Lekarza/Guide for GPs, 2012)
Atherosclerosis can begin in the developmental age. Further cardio-vascular side effects are dependent upon earlier appearing of risk factors such as: dyslipidaemia, overweight, bad eating habits, smoking and hypertension. Clinical atherogenesis manifestation depends also on family predispositions and widely understood influence of environmental factors. According to contemporary recommendations early prevention of cardiovascular diseases aimed at children and youth population should be conducted in three fields: health promotion, children and youth identification with large risk of cardiovascular diseases prevalence and correctly defined and conducted intervention in selected group of people with high risk of atherosclerosis related diseases.